Strategic insights from clustering analysis of essential oil sales in UMKM: A comprehensive study on product types, sizes, couriers, and distribution across Indonesian Provinces - Novianti Madhona Faizah; Desyi Erawati; Shirlyani Shirlyani; Luky Fabrianto; Tiwuk Wahyuli Prihandayani (Institute of Computer Science (IOCS), 2024)
This study explores the sales transactions of a Micro, Small, and Medium Enterprise (UMKM) that sells over 40 types of essential oils, totaling 2305 items sold in 2023. The products, packaged in small bottles (10-50 ml), were distributed to almost every province in Indonesia. The main objective is to cluster the data based on variables such as oil type, bottle size, courier company, and destination province. The elbow method determined an optimal number of clusters (k=4), and the Silhouette Coefficient validated the effectiveness of the clustering (0.7614). To simplify the complex clustering results, Principal Component Analysis (PCA) was used for visualization, providing a clear representation of 5 variables and 4 clusters. This study offers valuable insights for informed decision-making in UMKM's service enhancement and development